2-Mercaptobenzothiazole clay as matrix for sorption and preconcentration of some heavy metals from aqueous solution - Dias Filho, Newton L. [UNESP]; Gushikem, Yoshitaka; Polito, Wagner L. (Elsevier, 1995)
2-Mercaptobenzothiazole loaded on previously polystyrene treated clay was prepared, characterized and used for sorption and preconcentration of Hg(II) Pb(II), Zn(II) and Cd(II) from an aqueous solution. The support used was a natural clay previously treated with sulphuric acid solution. Adsorptiou isotherms of metal ions from aqueous solutions as function of pH were studied at 298 K. Conditions for quantitative retention and elution were established for each metal by batch and column methods. The chemically treated clay was very selective to Hg(II) in solution in which Zn(II), Cd(II), Pb(II) and some transition metal ions were also present.
Keywords: 2-Mercaptobenzothiazole; Clay; Heavy metal adsorption; Metals; Preconcentration; 2 mercaptobenzothiazole; heavy metal; adsorption; methodology; priority journal